Transcriptome analysis reveals distinct gene expression profiles in astrocytoma grades II-IV - Nato Narsia; Pradeep Ramagiri; Jiri Ehrmann; Zdenek Kolar (Biomedical Papers, 2017)
Background: Astrocytoma is the most prevalent form of primary brain cancer categorized into four histological grades by the World Health Organization. Investigation into individual grades of astrocytoma by previous studies has provided some insight into dysregulation of regulatory networks associated with increasing astrocytoma grades. However, further understanding of key mechanisms that distinguish different astrocytoma grades is required to facilitate targeted therapies. Methods: In this study, we utilized a large cohort of publicly available RNA sequencing data from patients with diffuse astrocytoma (grade II), anaplastic astrocytoma (grade III), primary glioblastoma (grade IV), secondary glioblastoma (grade IV), recurrent glioblastoma (grade IV), and normal brain samples to identify genetic similarities and differences between these grades using bioinformatics applications. Results: Our analysis revealed a distinct gene expression pattern between grade II astrocytoma and grade IV glioblastoma (GBM). We also identified genes that were exclusively expressed in each of the astrocytoma grades. Furthermore, we identified known and novel genes involved in key pathways in our study. Gene set enrichment analysis revealed a distinct expression pattern of transcriptional regulators in primary GBM. Further investigation into molecular processes showed that the genes involved in cell proliferation and invasion were shared across all subtypes of astrocytoma. Also, the number of genes involved in metastasis, regulation of cell proliferation, and apoptosis increased with tumor grade. Conclusions: We confirmed existing findings and shed light on some important genes and molecular processes that will improve our understanding of glioma biology.